Rapid microwave sintering of alumina ceramics with an addition of carbon nanotubes. Issue 4 (15th February 2021) - Egorov, S.V.; Eremeev, A.G.; Kholoptsev, V.V.; Plotnikov, I.V.; Rybakov, K.I.; Sorokin, A.A.; Balabanov, S.S.; Rostokina, E.Ye.; Bykov, Yu.V.
Abstract: Compacted alumina samples with an addition of 1.0 and 2.5 wt % carbon nanotubes (CNT) have been microwave sintered at heating rates 50 and 100°С/min to a maximum temperature of 1550–1600°С with zero hold time. The densification kinetics has been studied using optical dilatometry. No noticeable influence of CNT on the development of thermal instability during rapid microwave sintering of alumina has been detected. The relative densities of the samples containing 1.0 and 2.5 wt % CNT sintered at a maximum temperature of 1550 °C and zero hold time were 93.8 and 87.5%, respectively. Microwave sintering with a repeated development of thermal instability has resulted in an increase in the final density to 95.0%.